A BIBLIOMETRIC ANALYSIS: COMPREHENSIVE OVERVIEW OF ISLAMIC MONETARY POLICY - Mukti, Titania; Mahfud, Alvin; Ayu, Kayla Annisa; Zahra, Andin (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 10 No 1 (2024): The 10th International Conference of Islamic Economics and Business (ICONIES 2024), 2024)
This study presents a bibliometric analysis of Islamic monetary policy research from Scopus-indexed scientific publications. Data sources were obtained from searches using the publish or perish application with the keywords monetary policy and Islam as many as 190 articles from 1990-2024. Statistical analysis of metadata using the VOS Viewer application. This study analyzes the trend of research development based on the year of publication of the work, journal contribution, journal citation, country of publication, co-authorship between countries, authors, keywords used, and cluster visualization analysis of the research landscape. The results show that the keywords "monetary policy" and "Islamic banks" can be said to be developing quite well because each year shows an increase in the number of studies relevant to these keywords. Research clusters consisting of 7 clusters. future research development directions future research recommendations can take the theme of the implementation of Islamic monetary policy in Muslim countries, challenges and obstacles to the implementation of Islamic monetary policy, and strategic models for implementing Islamic monetary policy.